Silver-containing zirconia sintered body, silver-containing stabilized zirconia powder, method for producing silver-containing stabilized zirconia powder, and method for producing silver-containing zirconia sintered body

By adding silver particles and stable zirconia to the zirconia sintered body, and forming a silver-containing zirconia sintered body through sintering, the problem of easy peeling of coated antibacterial substances is solved, and the durability and mechanical properties of antibacterial effects are improved.

CN119894847APending Publication Date: 2025-04-25DAIICHI KIGENSO KAGAKU KOGYO CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480004005.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-31
Filing Date
2024-03-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, antibacterial substances coated on the surface of zirconia sintered bodies are prone to peel off due to wear, resulting in low antibacterial durability.

Method used

Add silver particles and stabilize zirconia to the sintered zirconia body to form a sintered zirconia body to ensure the internal distribution of silver particles, thereby maintaining antibacterial effects.

Benefits of technology

By improving the dispersion of silver particles in the sintered silver zirconia body, a high relative sintering density is achieved, and the mechanical properties and hydrothermal aging resistance are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894847A_ABST
    Figure CN119894847A_ABST
Patent Text Reader

Abstract

Provided is a silver-containing zirconia sintered body containing silver particles, zirconia and a stabilizer, the silver particles having an average grain diameter of 0.5 [mu] m or less, the stabilized zirconia having an average grain diameter of 0.35 [mu] m or less, and the relative sintered density of 98% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a silver-containing zirconia sintered body, a silver-containing stabilized zirconia powder, a method for producing the silver-containing stabilized zirconia powder, and a method for producing the silver-containing zirconia sintered body. Background Art

[0002] As a method for making zirconia ceramics (zirconia sintered bodies) have antibacterial effects, a common method is to coat the ceramic surface with an antibacterial substance. As the antibacterial substance, silver, which has a broad spectrum of antibacterial properties, and titanium oxide, which serves as a photocatalyst, are used.

[0003] Silver is used in restorations such as dental implants to inhibit the formation of biofilms that lead to infection. Non-Patent Documents 1 and 2 disclose coating restorations with silver nanoparticles to impart an antibacterial effect.

[0004] In addition, conventionally, ceramic knives are sold that have titanium oxide coated on the surface by firing to give them an antibacterial effect.

[0005] Prior art literature

[0006] Non-patent literature

[0007] Non-patent document 1: Kaijin Xu, Ceram. Int., 2011, 37, p2109-2115. “Microorganism adhesion inhibited by silver doped Yttria-stabilized zirconia ceramics”.

[0008] Non-patent document 2: Yamada, R., Mater. Sci. Eng. C, 2017, 78, p1054-1060. “Agnanoparticle-coated zirconia for antibacterial prosthesis”. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, the coating as described above may peel off due to wear and tear, and the durability of the antibacterial effect is low.

[0011] After intensive research, the inventors came up with the idea that if antibacterial substances could be added to the system of zirconia sintered bodies, it would be possible to suppress the reduction of antibacterial effects caused by wear.

[0012] Compared with copper and zinc, which also have antibacterial effects, silver is considered to have a broader antibacterial spectrum and stronger antibacterial effect. However, after further research, the inventors found that when silver and stabilized zirconium oxide are mixed to form silver-containing zirconium oxide powder, and the silver-containing zirconium oxide powder is sintered to form a zirconium oxide sintered body, the mechanical properties, sinterability and hydrothermal aging resistance are significantly reduced.

[0013] It should be noted that even if copper and zinc are mixed with stabilized zirconia and sintered, the sinterability and hydrothermal aging resistance are not reduced.

[0014] The present invention is made in view of the above problems, and its purpose is to provide a silver-containing zirconia sintered body, which has excellent mechanical properties, sinterability and hydrothermal aging resistance. In addition, it is also to provide a silver-containing stable zirconia powder, which can be obtained by sintering. In addition, it is also to provide a method for producing the silver-containing stable zirconia powder. In addition, it is also to provide a method for producing the silver-containing zirconia sintered body.

[0015] Solutions for solving problems

[0016] In view of the above problems, the inventors conducted in-depth research on silver-containing zirconia sintered bodies and found that the following structure can provide a silver-containing zirconia sintered body with excellent mechanical properties, sinterability and hydrothermal aging resistance, thereby completing the present invention.

[0017] That is, the present invention provides the following contents.

[0018] [1] A silver-containing zirconium oxide sintered body, comprising:

[0019] Silver particles; and

[0020] Stabilized zirconium oxide, comprising zirconium oxide and a stabilizer, wherein:

[0021] The average particle size of the silver particles is less than 0.5 μm,

[0022] The average grain size of the stabilized zirconium oxide is less than 0.35 μm.

[0023] The relative sintering density is above 98%.

[0024] According to the configuration of [1], the silver particles are not coated on the surface of the sintered body but are contained in the silver-containing zirconia sintered body itself. Therefore, even if the surface of the silver-containing zirconia sintered body is worn, the silver particles are exposed from the inside and the antibacterial effect can be maintained.

[0025] In addition, since silver has excellent ductility and malleability, it is difficult to reduce it to fine particles by pulverizing. However, in the present invention, the silver particles in the silver-containing zirconia sintered body can be reduced to fine particles by adopting the manufacturing method described below. Specifically, the average particle size of the silver particles can be set to 0.5 μm or less. When the silver particles are fine particles, the segregation of the silver particles in the silver-containing zirconia sintered body can be suppressed. As a result, sintering can be performed at a low temperature. In addition, the reduction in mechanical properties can be suppressed. That is, by improving the dispersibility of the silver particles in the silver-containing zirconia sintered body, densification can be achieved (the relative sintering density can be increased), and the reduction in mechanical properties of the silver-containing zirconia sintered body can be suppressed. Specifically, by setting the relative sintering density to 98% or more, the reduction in mechanical properties of the silver-containing zirconia sintered body can be suppressed.

[0026] In addition, a high sintering temperature (for example, exceeding 1500° C.) can also improve the relative sintering density. However, when the sintering temperature is high, the grain size of zirconium oxide increases, resulting in a decrease in hydrothermal aging resistance.

[0027] However, in the present invention, the sintering temperature is relatively low, and the average crystal grain size of the stabilized zirconia can be made 0.35 μm or less. As a result, the reduction in hydrothermal aging resistance can be suppressed.

[0028] As described above, according to the configuration of [1], the average particle size of the silver particles is 0.5 μm or less, which can suppress the reduction of sinterability, and can achieve densification (relative sintering density of 98% or more), which can suppress the reduction of mechanical properties. In addition, since the average grain size of the stabilized zirconia is 0.35 μm or less, the reduction of hydrothermal aging resistance can be suppressed.

[0029] Furthermore, the present invention also provides the following contents.

[0030] [2] The silver-containing zirconia sintered body according to [1], wherein the average grain size of the stabilized zirconia is 0.25 μm or less.

[0031] When the average crystal grain size of the stabilized zirconia is 0.25 μm or less, it can be said that the sintering temperature is lower.

[0032] Furthermore, the present invention also provides the following contents.

[0033] [3] The silver-containing zirconium oxide sintered body according to [1] or [2], comprising silver particles in a range of 0.025 mass % to 20 mass % as Ag2O, when the total amount of zirconium oxide and the stabilizer is 100 mass %.

[0034] When the content of the silver particles is 0.025 mass % or more, the antibacterial property is excellent. Moreover, when the content of the silver particles is 20 mass % or less, the mechanical properties and sinterability are more excellent.

[0035] Furthermore, the present invention also provides the following contents.

[0036] [4] The silver-containing zirconia sintered body according to any one of [1] to [3], which has a three-point bending strength of 600 MPa or more.

[0037] When the three-point bending strength is 600 MPa or more, it can be said that the strength is higher.

[0038] Furthermore, the present invention also provides the following contents.

[0039] [5] The silver-containing zirconia sintered body according to any one of [1] to [4], wherein the toughness value according to the IF method is 5 MPa·m 0.5 above.

[0040] When the toughness value is 5MPa·m 0.5 When it is above, it can be said that the toughness is higher.

[0041] Furthermore, the present invention also provides the following contents.

[0042] [6] The silver-containing zirconia sintered body according to any one of [1] to [5], wherein the monoclinic crystal ratio after hydrothermal treatment at 134° C. and 0.3 MPa for 15 hours is 10% or less.

[0043] When the monoclinic crystal ratio after hydrothermal treatment at 134° C. and 0.3 MPa for 15 hours is 10% or less, it can be said that the hydrothermal aging resistance is more excellent.

[0044] Furthermore, the present invention also provides the following contents.

[0045] [7] According to the silver-containing zirconia sintered body described in any one of [1] to [6], the stabilizer is one or more selected from the group consisting of Y2O3, CeO2, Er2O3 and CaO.

[0046] When the stabilizer is one or more selected from the group consisting of Y2O3, CeO2, Er2O3 and CaO, low temperature sinterability and mechanical strength are more excellent.

[0047] Furthermore, the present invention also provides the following contents.

[0048] [8] The silver-containing zirconia sintered body according to any one of [1] to [7], wherein the content of the stabilizer is 15 mol% or less when the zirconia and the stabilizer are taken as a whole.

[0049] When the content of the stabilizer is 15 mol % or less, the mechanical strength is more excellent.

[0050] Furthermore, the present invention also provides the following contents.

[0051] [9] A silver-stabilized zirconium oxide powder, comprising:

[0052] Stabilized zirconium oxide, comprising zirconium oxide and a stabilizer; and

[0053] Silver and / or silver oxide having an average particle size of 0.5 μm or less.

[0054] Silver oxide particles become silver particles after thermal decomposition. According to the silver-containing stabilized zirconia powder [9], since it contains stabilized zirconia and silver and / or silver oxide with an average particle size of 0.5 μm or less, the silver-containing stabilized zirconia powder is sintered to obtain a sintered body containing silver (silver particles) with an average particle size of 0.5 μm or less.

[0055] That is to say, in any of the following cases, namely: when the silver-containing stabilized zirconia powder contains only silver oxide with an average particle size of less than 0.5 μm; when the silver-containing stabilized zirconia powder contains both silver with an average particle size of less than 0.5 μm and silver oxide with an average particle size of less than 0.5 μm; and when the silver-containing stabilized zirconia powder contains only silver with an average particle size of less than 0.5 μm, the silver oxide particles will all become silver particles after thermal decomposition, and therefore, by sintering the silver-containing stabilized zirconia powder, a sintered body containing silver (silver particles) with an average particle size of less than 0.5 μm can be obtained.

[0056] In particular, according to the configuration of [9], the average particle size of silver and / or silver oxide is reduced to 0.5 μm or less and is highly dispersed in the stabilized zirconium oxide powder. As a result, the grain size of the stabilized zirconium oxide in the zirconium oxide sintered body obtained by sintering can be easily controlled to 0.35 μm or less, thereby achieving the desired hydrothermal aging performance and mechanical properties.

[0057] Furthermore, the present invention also provides the following contents.

[0058]

[10] According to the silver-containing stabilized zirconia powder described in [9], within the range of 10 nm to 0.5 μm of pore distribution based on mercury intrusion porosimetry, the peak diameter of the pore volume distribution is 30 nm to 100 nm, the pore volume is 0.25 ml / g to 0.46 ml / g, and the pore distribution width is 40 nm to 120 nm.

[0059] In addition to reducing the average particle size of silver and / or silver oxide to less than 0.5 μm and highly dispersing silver and / or silver oxide in the stabilized zirconia powder, if the pore distribution of the silver-containing stabilized zirconia powder is controlled (optimized) as described

[10] , the grain size of the stabilized zirconia in the sintered zirconia sintered body can be easily controlled to less than 0.25 μm, thereby obtaining the desired hydrothermal aging properties and mechanical properties.

[0060] Furthermore, the present invention also provides the following contents.

[0061]

[11] A method for producing silver-containing stabilized zirconium oxide powder, comprising: a step of mixing stabilized zirconium oxide containing zirconium oxide and a stabilizer with silver oxide having an average particle size of not more than 0.5 μm.

[0062] Silver is difficult to pulverize into fine particles due to its excellent ductility and malleability, but silver oxide can be pulverized into fine particles due to its characteristics.

[0063] According to the configuration of

[10] , silver oxide finely granulated to an average particle size of 0.5 μm or less is mixed with stabilized zirconium oxide to obtain zirconium oxide powder containing stabilized zirconium oxide and silver oxide with an average particle size of 0.5 μm or less. The silver oxide particles are heated and thermally decomposed to form silver particles. Therefore, the silver-containing stabilized zirconium oxide powder obtained by the manufacturing method of

[10] is sintered to obtain a sintered body containing silver (silver particles) with an average particle size of 0.5 μm or less.

[0064] Furthermore, the present invention also provides the following contents.

[0065]

[12] A method for producing a silver-containing zirconium oxide sintered body, comprising:

[0066] Step X, forming the silver-containing stabilized zirconia powder described in [9] or

[10] to obtain a formed body; and

[0067] Step Y is, after the step X, sintering the molded body at a temperature of 1250° C. to 1500° C. for 1 hour to 5 hours.

[0068] According to the configuration

[12] , since the silver-containing stabilized zirconia powder described in [9] or

[10] is used, a sintered body with a high sintering density can be obtained under low-temperature sintering conditions of 1250° C. to 1500° C. Furthermore, since the sintering is performed at a low temperature, the obtained sintered body has excellent resistance to hydrothermal aging.

[0069] Effects of the Invention

[0070] According to the present invention, a silver-containing zirconium oxide sintered body having excellent mechanical properties, sinterability and hydrothermal aging resistance can be provided. In addition, a silver-containing stabilized zirconium oxide powder can be provided, and the silver-containing zirconium oxide sintered body can be obtained by sintering. In addition, a method for producing the silver-containing stabilized zirconium oxide powder can be provided. In addition, a method for producing the silver-containing zirconium oxide sintered body can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 This is a schematic diagram for explaining the method for producing the silver-containing stabilized zirconia powder according to the present embodiment.

[0072] Figure 2 A schematic diagram for explaining the indentation length and crack length. DETAILED DESCRIPTION

[0073] The embodiments of the present invention are described below. However, the present invention is not limited to these embodiments. It should be noted that in this specification, zirconium oxide (zirconium dioxide) is ordinary zirconium oxide containing less than 10% by mass of an impurity metal compound containing hafnium. In addition, in this specification, expressions such as "containing" and "including" include the concepts of "containing", "including", "substantially consisting of..." and "consisting only of...".

[0074] [Silver-containing zirconia sintered body]

[0075] Hereinafter, an example of the silver-containing zirconia sintered body of the present embodiment will be described. However, the silver-containing zirconia sintered body of the present invention is not limited to the following example.

[0076] The silver-containing zirconia sintered body of the present embodiment includes:

[0077] Silver particles; and

[0078] Stabilized zirconium oxide, comprising zirconium oxide and a stabilizer.

[0079] That is, it contains silver particles, zirconium oxide and stabilizers.

[0080] The average particle size of the silver particles is less than 0.5 μm,

[0081] The average grain size of the stabilized zirconium oxide is less than 0.35 μm.

[0082] The relative sintering density is above 98%.

[0083] The silver-containing zirconia sintered body contains silver particles. The average particle size of the silver particles is less than 0.5 μm. Since the average particle size of the silver particles is less than 0.5 μm, the segregation of the silver particles in the silver-containing zirconia sintered body can be suppressed. As a result, the reduction in sinterability can be suppressed. In addition, the reduction in mechanical properties can also be suppressed. That is, by improving the dispersibility of the silver particles in the silver-containing zirconia sintered body, densification can be achieved (the relative sintering density can be increased), and the reduction in mechanical properties of the silver-containing zirconia sintered body can be suppressed.

[0084] The average particle size of the silver particles is preferably 0.4 μm or less. The smaller the average particle size of the silver particles, the better, for example, 0.05 μm or more, 0.1 μm or more, etc.

[0085] The average particle size of the silver particles is preferably from 0.05 μm to 0.5 μm, and more preferably from 0.1 μm to 0.4 μm.

[0086] The method for determining the average particle size of the silver particles shall be based on the method described in the examples.

[0087] When the total amount of zirconium oxide and stabilizer is set to 100 mass%, the content of the silver particles is preferably in the range of 0.025 mass% to 20 mass% in terms of Ag2O. When the content of the silver particles is 0.025 mass% or more, the antibacterial property is excellent. Moreover, when the content of the silver particles is 20 mass% or less, the mechanical properties and sintering properties are more excellent.

[0088] When the total amount of zirconium oxide and the stabilizer is set to 100 mass%, the content of the silver particles is more preferably 0.05 mass% or more, further preferably 0.1 mass% or more, and particularly preferably 0.5 mass% or more, calculated as Ag2O.

[0089] When the total amount of zirconium oxide and the stabilizer is set to 100 mass%, the content of the silver particles is more preferably 16 mass% or less, further preferably 12 mass% or less, and particularly preferably 10 mass% or less, calculated as Ag2O.

[0090] When the total amount of zirconium oxide and the stabilizer is set to 100 mass%, the content of the silver particles, calculated as Ag2O, is more preferably from 0.05 mass% to 16 mass%, further preferably from 0.1 mass% to 12 mass%, and particularly preferably from 0.5 mass% to 10 mass%.

[0091] The silver-containing zirconia sintered body includes stabilized zirconia, and the stabilized zirconia includes zirconia and a stabilizer.

[0092] When the silver-containing zirconia sintered body is taken as 100 mass%, the total content of zirconium oxide and stabilizer (content of stabilized zirconium oxide) in the silver-containing zirconia sintered body is preferably 70 mass% or more, and more preferably 80 mass% or more. When the silver-containing zirconia sintered body is taken as 100 mass%, the total content of zirconium oxide and stabilizer can be 99.9 mass% or less, 99 mass% or less, etc.

[0093] When the entire silver-containing zirconia sintered body is taken as 100 mass %, the total content of zirconium oxide and the stabilizer in the silver-containing zirconia sintered body is more preferably 70 mass % to 99.9 mass %, and further preferably 80 mass % to 99.9 mass %.

[0094] The stabilizer is preferably an oxide of at least one selected from alkaline earth metals and rare earth elements. The alkaline earth metals are Ca, Sr, Ba, and Ra. The rare earth elements are Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Among them, the stabilizer is preferably at least one selected from the group consisting of Y2O3, CeO2, Er2O3, and CaO. When the stabilizer is at least one selected from the group consisting of Y2O3, CeO2, Er2O3, and CaO, low temperature sintering and mechanical strength are more excellent.

[0095] When zirconium oxide and the stabilizer are considered as a whole, the content of the stabilizer is preferably 15 mol% or less. When the content of the stabilizer is 15 mol% or less, mechanical strength is more excellent.

[0096] The content of the stabilizer is preferably 1.4 mol % or more, more preferably 1.5 mol % or more, and further preferably 1.6 mol % or more.

[0097] The content of the stabilizer is preferably 14 mol % or less, more preferably 13 mol % or less, and further preferably 12.5 mol % or less.

[0098] The content of the stabilizer is more preferably 1.4 mol % to 14 mol %, further preferably 1.5 mol % to 13 mol %, and particularly preferably 1.6 mol % to 12.5 mol %.

[0099] When zirconium oxide and a stabilizer are taken as a whole, if Y2O3 is used as the stabilizer, the content of Y2O3 is preferably 1.4 mol% or more and 7.5 mol% or less. The content of Y2O3 is more preferably 1.5 mol% or more, and further preferably 1.6 mol% or more. The content of Y2O3 is more preferably 6.5 mol% or less, further preferably 6 mol%, particularly preferably 5.6 mol% or less, particularly preferably 5 mol% or less, and particularly preferably 4.5 mol% or less. When the content of Y2O3 is 1.4 mol% or more and 7.5 mol% or less, the mechanical strength of the silver-containing zirconium oxide sintered body is more excellent.

[0100] When zirconium oxide and the stabilizer are taken as a whole, if Y2O3 is used as the stabilizer, the content of Y2O3 is more preferably from 1.5 mol% to 6.5 mol%, and further preferably from 1.6 mol% to 6 mol%.

[0101] When the zirconium oxide and the stabilizer are taken as a whole, if CeO2 is used as the stabilizer, the content of the CeO2 is preferably 10 mol% to 15 mol%. The content of the CeO2 is more preferably 11 mol% to 11.5 mol%. The content of the CeO2 is more preferably 14 mol% to 13 mol%, more preferably 12.5 mol% to 14 mol%, especially preferably 12 mol% to 12 mol%. When the content of the CeO2 is 10 mol% to 15 mol%, the mechanical strength of the silver-containing zirconium oxide sintered body is better. Among them, the content of the CeO2 is preferably 10 mol% to 14 mol%.

[0102] When zirconium oxide and the stabilizer are taken as a whole, if CeO2 is used as the stabilizer, the content of CeO2 is more preferably from 11 mol% to 14 mol%, further preferably from 11.5 mol% to 13 mol%, and particularly preferably from 11.5 mol% to 12.5 mol%.

[0103] When zirconium oxide and a stabilizer are taken as a whole, if any one of Sc2O3, Er2O3, and Yb2O3 is used as the stabilizer, its content is preferably 1.4 mol% or more and 7.5 mol% or less. When any one of Sc2O3, Er2O3, and Yb2O3 is used, the content is more preferably 1.5 mol% or more, and further preferably 1.6 mol% or more. When any one of Sc2O3, Er2O3, and Yb2O3 is used, the content is more preferably 6.5 mol% or less, further preferably 6 mol%, particularly preferably 5.6 mol% or less, particularly preferably 5 mol% or less, and particularly preferably 4.5 mol% or less. When the content of any one of Sc2O3, Er2O3, and Yb2O3 is 1.4 mol% or more and 7.5 mol% or less, the mechanical strength of the silver-containing zirconium oxide sintered body is more excellent.

[0104] When zirconium oxide and the stabilizer are taken as a whole, if any one of Sc2O3, Er2O3, and Yb2O3 is used as the stabilizer, the content thereof is more preferably from 1.5 mol% to 6.5 mol%, and further preferably from 1.6 mol% to 6 mol%.

[0105] When zirconium oxide and a stabilizer are taken as a whole, if CaO is used as the stabilizer, the content of CaO is preferably 3.5 mol% or more and 15 mol% or less. The content of CaO is more preferably 3.8 mol% or more, and further preferably 4.0 mol% or more. The content of CaO is more preferably 12.0 mol% or less, and further preferably 9.0 mol% or less. When the content of CaO is 3.5 mol% or more and 15 mol% or less, the mechanical strength of the silver-containing zirconium oxide sintered body is more excellent.

[0106] When zirconium oxide and the stabilizer are considered as a whole, if CaO is used as the stabilizer, the content of CaO is more preferably 3.8 mol % to 12 mol %, and further preferably 4 mol % to 9 mol %.

[0107] When zirconium oxide and stabilizer are taken as a whole, if CaO and Y2O3 are used as the stabilizer, the total amount of the stabilizer is 2.5 mol% to 6.5 mol% in terms of oxide, and the ratio of [CaO amount (mol%)] / [total amount of stabilizer (mol%)] is preferably 50% to 98%.

[0108] The ratio of [the amount of CaO (mol%)] / [the total amount of stabilizers (mol%)] is more preferably 55% or more, and further preferably 60% or more.

[0109] The ratio of [the amount of CaO (mol%)] / [the total amount of the stabilizer (mol%)] is more preferably 90% or less, and further preferably 80% or less.

[0110] The ratio of [amount of CaO (mol%)] / [total amount of stabilizer (mol%)] is more preferably 55% to 90%, and further preferably 60% to 80%.

[0111] When zirconium oxide and stabilizer are taken as a whole, if CaO and Y2O3 are used as the stabilizer, the total amount of the stabilizer is preferably 2.5 mol% or more and 6.5 mol% or less in terms of oxide. When the total amount of the stabilizer is 2.5 mol% or more in terms of oxide, the monoclinic phase ratio in the obtained zirconium oxide sintered body can be reduced, and cracking of the zirconium oxide sintered body obtained by sintering the zirconium oxide powder can be prevented. Moreover, when the total amount of the stabilizer is 6.5 mol% or less in terms of oxide, the cubic phase ratio with lower mechanical properties (strength, toughness) can be reduced, and the tetragonal phase ratio with higher mechanical properties can be increased.

[0112] The total amount of the stabilizer is preferably 2.7 mol % or more, more preferably 2.9 mol % or more, and further preferably 3.0 mol % or more, in terms of oxide.

[0113] The total amount of the stabilizer, calculated as oxide, is preferably 6.0 mol % or less, more preferably 5.5 mol % or less, further preferably 5.0 mol % or less, and particularly preferably 4.5 mol % or less.

[0114] The total amount of the stabilizer, calculated as oxide, is preferably 2.7 mol % to 6.0 mol %, more preferably 2.9 mol % to 5.5 mol %, further preferably 3.0 mol % to 5.0 mol %, particularly preferably 3.0 mol % to 4.5 mol %.

[0115] The average grain size of the stabilized zirconia is less than 0.35 μm. Since the average grain size of the stabilized zirconia is less than 0.35 μm, the hydrothermal aging resistance is excellent. It should be noted that when the sintering temperature is high, the grain size of the stabilized zirconia increases, but since the average grain size of the stabilized zirconia is less than 0.35 μm, it can be said that the sintering temperature is low.

[0116] The average grain size of the stabilized zirconia is preferably 0.3 μm or less, more preferably 0.25 μm or less, and further preferably 0.2 μm or less. The smaller the average grain size of the stabilized zirconia, the better, for example, 0.05 μm or more, 0.1 μm or more.

[0117] The average grain size of the stabilized zirconia is preferably 0.05 μm to 0.3 μm, more preferably 0.05 μm to 0.25 μm. The average grain size of the stabilized zirconia is determined by the method described in the examples.

[0118] The silver-containing zirconia sintered body may contain Al2O3 (aluminum oxide) in a range of 25% by mass or less when the total amount of zirconium oxide and the stabilizer is set to 100% by mass. When the alumina is contained in a range of 25% by mass or less, the alumina is used as a sintering aid in the process of sintering the zirconium oxide powder to obtain the silver-containing zirconia sintered body.

[0119] If the silver-containing zirconia sintered body contains Al 2 O 3 , the content of Al 2 O 3 is more preferably 10% by mass or less, and further preferably 1% by mass or less, from the viewpoint of well exerting the function of a sintering aid.

[0120] If the silver-containing zirconia sintered body contains Al 2 O 3 , the content of Al 2 O 3 is more preferably 0.1 mass % or more, and further preferably 0.25 mass % or more, from the viewpoint of well exerting the function of a sintering aid.

[0121] When the silver-containing zirconia sintered body contains Al 2 O 3 , the content of Al 2 O 3 is more preferably 0.1 mass % to 10 mass %, and further preferably 0.25 mass % to 1 mass %.

[0122] In order to improve the properties such as strength, the silver-containing zirconia sintered body may further contain sinterable ceramics or thermosetting resins in addition to alumina.

[0123] The silver-containing zirconia sintered body may contain one or more selected from the group consisting of Fe, V, Mn, Co, Zn, Cu and Ti. When the silver-containing zirconia sintered body contains one or more selected from the group consisting of Fe, V, Mn, Co, Zn, Cu and Ti, it can be well colored.

[0124] <Monoclinic phase ratio before hydrothermal treatment>

[0125] The monoclinic phase ratio (monoclinic phase ratio before hydrothermal treatment) contained in the crystal phase of the silver-containing zirconia sintered body is preferably 0% or more and 10% or less. The monoclinic phase ratio is preferably 0%, and can be 0.1% or more, 0.5% or more, etc. The monoclinic phase ratio is more preferably 5% or less, and further preferably 1% or less.

[0126] The monoclinic phase ratio is more preferably 0% to 10%, and even more preferably 0% to 1%.

[0127] When the monoclinic phase ratio is 0% or more and 10% or less, the mechanical properties (bending strength, fracture toughness value) are more excellent.

[0128] The monoclinic phase ratio can be controlled by, for example, the average particle size of silver particles, the content of silver particles, the content and proportion of the stabilizer, the sintering temperature, and the like.

[0129] The method for calculating the monoclinic phase ratio shall be based on the method described in the examples.

[0130] <Anti-hydrothermal aging>

[0131] The monoclinic phase ratio of the silver-containing zirconia sintered body after hydrothermal treatment for 15 hours at 134°C and 0.3MPa (absolute pressure of 0.3MPa) is preferably 80% or less. When the monoclinic phase ratio after the hydrothermal treatment is 80% or less, it can be said that the hydrothermal aging resistance is more excellent. The monoclinic phase ratio after the hydrothermal treatment can be controlled, for example, by the average particle size of the silver particles, the content of the silver particles, the content of the stabilizer, the proportion contained, the sintering temperature, etc.

[0132] The monoclinic phase ratio after the hydrothermal treatment is more preferably 50% or less, and further preferably 10% or less. The smaller the monoclinic phase ratio after the hydrothermal treatment, the better, for example, 0.1% or more, 0.5% or more.

[0133] The monoclinic phase ratio after the hydrothermal treatment is more preferably 0% to 50% and even more preferably 0% to 10%.

[0134] <Mechanical strength>

[0135] The three-point bending strength of the silver-containing zirconia sintered body is preferably 600 MPa or more.

[0136] The three-point bending strength is more preferably 700 MPa or more, and further preferably 800 MPa or more. The greater the three-point bending strength, the better, and can be, for example, 1500 MPa or less, 1200 MPa or less, etc.

[0137] The three-point bending strength is more preferably 700 MPa to 1500 MPa, and further preferably 800 MPa to 1500 MPa.

[0138] When the three-point bending strength is 600 MPa or more, it can be said that the strength is higher. The method for calculating the three-point bending strength is based on the method described in the examples.

[0139] <Toughness>

[0140] The toughness value of the silver-containing zirconia sintered body according to the IF method is preferably 5 MPa·m 0.5 above.

[0141] The toughness value is more preferably 6 MPa·m 0.5 More preferably, 10 MPa·m 0.5 The larger the toughness value, the better, for example, it can be 20MPa·m 0.5 Below, 25MPa·m 0.5 The following etc.

[0142] The toughness value is more preferably 6 MPa·m 0.5 Above 20MPa·m 0.5 Below, more preferably 10 MPa·m 0.5 Above 20MPa·m 0.5 the following.

[0143] When the toughness value is 5MPa·m 0.5 When the toughness is higher than 0.05, the toughness can be said to be higher. The method for calculating the toughness value shall be based on the method described in the embodiment.

[0144] <Relative sintered density>

[0145] The relative sintering density of the silver-containing zirconia sintered body is preferably 98% or more, more preferably 98.5% or more. When the relative sintering density is 98% or more, it can be said that the sintering of the silver-containing zirconia sintered body is relatively sufficient. Moreover, when the relative sintering density is 98% or more, it can be said that the strength of the silver-containing zirconia sintered body is higher.

[0146] <Method for measuring relative sintered density of silver-containing zirconia sintered body>

[0147] The relative sintered density is the relative sintered density expressed by the following formula (1):

[0148] Relative sintered density (%) = (sintered density / theoretical sintered density) × 100···(1).

[0149] The theoretical sintered density (denoted as ρ0) is the value calculated by the following formula (2-1):

[0150] ρ0=(100+Y+Z) / [(100 / ρz)+(Y / 3.987)+(Z / 10.49)]···(2-1).

[0151] Wherein, Y is the aluminum oxide concentration (weight %), and Z is the silver concentration (weight %). When silver oxide is used as a raw material, the silver concentration (weight %) is calculated according to formula (2-2):

[0152] Z=[107.868×(silver oxide concentration (weight %))] / (231.736×2)···(2-2).

[0153] ρz is the value calculated by the following formula (2-3):

[0154] ρz=[124.25(100-X)+[molecular weight of stabilizer]×X] / 150[150.5(100+X)A 2 C]···(2-3).

[0155] Among them, if the stabilizer is Y2O3, the molecular weight of the stabilizer is 225.81, if the stabilizer is Er2O3, the molecular weight of the stabilizer is 382.52, and if the stabilizer is Yb2O3, the molecular weight of the stabilizer is 394.11.

[0156] In addition, X is the stabilizer concentration (mol %). And, A and C are values ​​calculated by the following formulas (2-4) and (2-5), respectively:

[0157] A=0.5080+0.06980X / (100+X)···(2-4);

[0158] C=0.5195-0.06180X / (100+X)···(2-5).

[0159] In formula (1), the theoretical sintered density varies depending on the powder composition.

[0160] For example, if the yttria content is 2 mol%, the theoretical sintered density of yttria-containing zirconium oxide is 6.117 g / cm 3 If the yttria content is 3 mol%, the theoretical sintered density of yttria-containing zirconium oxide is 6.098 g / cm 3 If the yttria content is 5.5 mol%, the theoretical sintered density of yttria-containing zirconium oxide is 6.051 g / cm 3 (If Al2O3=0 weight %).

[0161] If the stabilizer is Sc2O3, ρz is the value calculated by the following formula (3):

[0162] ρz=-0.0402(molar concentration of Sc2O3)+6.1294···(3).

[0163] If the stabilizer is CaO, ρz is the value calculated by the following formula (3-1):

[0164] ρz=-0.0400(molar concentration of CaO)+6.1700···(3-1).

[0165] In addition, the theoretical sintered density (denoted as ρ1) when a colorant is included is:

[0166] ρ1=100 / [(Z / V)+(100-Z) / ρ0]···(2-5).

[0167] In addition, Z is the colorant concentration (weight %), V is the colorant theoretical density (g / cm 3 ).

[0168] The theoretical density of the colorant is: Fe2O3 is 5.24g / cm 3 , ZnO is 5.61g / cm 3 , MnO2 is 5.03g / cm 3 , CoO is 6.10 g / cm 3 , Cr2O3 is 5.22g / cm 3 , TiO2 is 4.23g / cm 3 , Tb4O7 is 7.80g / cm 3 , CuO is 6.31 g / cm 3 , V2O5 is 3.36g / cm 3 .

[0169] In addition, the sintered density was measured by the Archimedean method.

[0170] The silver-containing zirconia sintered body of the present embodiment can be obtained, for example, by the method for producing a silver-containing zirconia sintered body described below.

[0171] The silver-containing zirconia sintered body of the present embodiment can be used as industrial parts, aesthetic parts, and dental materials. More specifically, it can be used in jewelry, watch parts, watch dials, artificial teeth, molding parts, wear-resistant parts, chemical-resistant parts, and the like.

[0172] In particular, if the silver-containing zirconia sintered body is used to make a knife, the reduction of the antibacterial effect caused by wear and sharpening during use can be suppressed. In addition, since the low-temperature sintering improves the hydrothermal aging resistance, it can also exert stable mechanical properties even under conditions that cause hydrothermal aging such as dishwashers.

[0173] [Silver-Containing Stabilized Zirconia Powder]

[0174] The silver-stabilized zirconium oxide powder of this embodiment comprises:

[0175] Stabilized zirconium oxide, comprising zirconium oxide and a stabilizer; and

[0176] Silver and / or silver oxide having an average particle size of 0.5 μm or less.

[0177] The silver-containing stabilized zirconia powder comprises primary particles of stabilized zirconia with zirconia as the main component. All or part of the primary particles are agglomerated to form secondary particles. That is, the silver-containing stabilized zirconia powder comprises unagglomerated primary particles of stabilized zirconia and secondary particles formed by agglomeration of the primary particles.

[0178] However, in the silver-containing stabilized zirconia powder, the amount of primary particles that do not form secondary particles but exist in the state of non-agglomerated primary particles is extremely small, for example, less than 1% by mass of the entire primary particles (the total amount of non-agglomerated primary particles and primary particles agglomerated into secondary particles). In other words, the silver-containing stabilized zirconia powder may contain a very small amount of non-agglomerated primary particles, but most of it is composed of secondary particles.

[0179] It should be noted that "containing zirconium oxide as a main component" means that when the primary particles are set to 100% by mass, the primary particles contain 70% by mass or more of zirconium oxide. That is, in this specification, the primary particles containing zirconium oxide as a main component refer to primary particles containing 70% by mass or more of zirconium oxide. The content of zirconium oxide contained in the primary particles is preferably 74% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more.

[0180] <Composition>

[0181] The silver-containing stabilized zirconia powder of the present embodiment contains silver and / or silver oxide having an average particle size of 0.5 μm or less.

[0182] The silver oxide particles become silver particles after thermal decomposition. According to the silver-containing stabilized zirconia powder, since it contains stabilized zirconia and silver and / or silver oxide with an average particle size of 0.5 μm or less, the silver-containing stabilized zirconia powder is sintered to obtain a sintered body containing silver (silver particles) with an average particle size of 0.5 μm or less.

[0183] That is to say, in any of the following cases, namely: when the silver-containing stabilized zirconia powder contains only silver oxide with an average particle size of less than 0.5 μm; when the silver-containing stabilized zirconia powder contains both silver with an average particle size of less than 0.5 μm and silver oxide with an average particle size of less than 0.5 μm; and when the silver-containing stabilized zirconia powder contains only silver with an average particle size of less than 0.5 μm, the silver oxide particles will all become silver particles after thermal decomposition, and therefore, by sintering the silver-containing stabilized zirconia powder, a sintered body containing silver (silver particles) with an average particle size of less than 0.5 μm can be obtained.

[0184] It should be noted that in this specification, the average particle size of silver and / or silver oxide refers to the average particle size of silver and silver oxide as a whole, without distinguishing between silver and silver oxide. The method for determining the average particle size of silver and / or silver oxide shall be based on the method described in the examples.

[0185] The average particle size of the silver and / or silver oxide is preferably 0.4 μm or less, more preferably 0.3 μm or less. The smaller the average particle size of the silver and / or silver oxide, the better, for example, 0.01 μm or more, 0.05 μm or more.

[0186] The average particle size of the silver and / or silver oxide is preferably 0.01 μm to 0.4 μm, and more preferably 0.01 μm to 0.3 μm.

[0187] When the total amount of zirconium oxide and stabilizer is set to 100 mass%, the content of silver and / or silver oxide is preferably in the range of 0.025 mass% to 20 mass% in terms of Ag2O. When the content of silver and / or silver oxide is 0.025 mass% or more, the antibacterial property is excellent. Moreover, when the content of silver and / or silver oxide is 20 mass% or less, the sintering property is more excellent. Moreover, when the content of silver and / or silver oxide is 20 mass% or less, the mechanical properties of the obtained sintered body are more excellent.

[0188] When the total amount of zirconium oxide and the stabilizer is set to 100 mass%, the content of silver and / or silver oxide is more preferably 0.05 mass% or more, further preferably 0.1 mass% or more, and particularly preferably 0.5 mass% or more, calculated as Ag2O.

[0189] When the total amount of zirconium oxide and the stabilizer is set to 100 mass%, the content of silver and / or silver oxide is more preferably 16 mass% or less, further preferably 12 mass% or less, and particularly preferably 10 mass% or less, calculated as Ag2O.

[0190] When the total amount of zirconium oxide and the stabilizer is set to 100 mass%, the content of silver and / or silver oxide, calculated as Ag2O, is more preferably from 0.05 mass% to 16 mass%, further preferably from 0.1 mass% to 12 mass%, and particularly preferably from 0.5 mass% to 10 mass%.

[0191] The silver-containing stabilized zirconia powder contains stabilized zirconia, and the stabilized zirconia comprises zirconium oxide and a stabilizer.

[0192] The stabilized zirconia contains a stabilizer. The stabilizer is contained in the primary particles in the form of a solid solution or the like. Since the stabilizer is contained, the silver-containing stabilized zirconia powder can be well sintered at a low temperature.

[0193] The stabilizer is preferably an oxide of at least one selected from alkaline earth metals and rare earth elements. The alkaline earth metals are Ca, Sr, Ba, and Ra. The rare earth elements are Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Among them, the stabilizer is preferably at least one selected from the group consisting of Y2O3, CeO2, Er2O3, and CaO. When the stabilizer is at least one selected from the group consisting of Y2O3, CeO2, Er2O3, and CaO, the low-temperature sintering property is excellent, and the mechanical strength of the obtained sintered body is more excellent.

[0194] When the zirconium oxide and the stabilizer are considered as a whole, the content of the stabilizer is preferably 15 mol% or less. When the content of the stabilizer is 15 mol% or less, the mechanical strength of the obtained sintered body is more excellent.

[0195] The content of the stabilizer is preferably 1.4 mol % or more, more preferably 1.5 mol % or more, and further preferably 1.6 mol % or more.

[0196] The content of the stabilizer is preferably 14 mol % or less, more preferably 13 mol % or less, and further preferably 12.5 mol % or less.

[0197] The content of the stabilizer is more preferably 1.4 mol % to 14 mol %, further preferably 1.5 mol % to 13 mol %, and particularly preferably 1.6 mol % to 12.5 mol %.

[0198] When zirconium oxide and a stabilizer are taken as a whole, if Y2O3 is used as the stabilizer, the content of Y2O3 is preferably 1.4 mol% to 7.5 mol%. The content of Y2O3 is more preferably 1.5 mol% to 1.6 mol%, and more preferably 6 mol%, and more preferably 5.6 mol% to 5.6 mol%, and particularly preferably 4.5 mol% to 4.5 mol%. When the content of Y2O3 is 1.4 mol% to 7.5 mol%, the mechanical strength of the zirconium oxide sintered body obtained by sintering the silver-containing stabilized zirconium oxide powder is more excellent.

[0199] When zirconium oxide and the stabilizer are taken as a whole, if Y2O3 is used as the stabilizer, the content of Y2O3 is more preferably from 1.5 mol% to 6.5 mol%, and further preferably from 1.6 mol% to 6 mol%.

[0200] When zirconium oxide and a stabilizer are taken as a whole, if CeO2 is used as the stabilizer, the content of CeO2 is preferably 10 mol% to 15 mol%. The content of CeO2 is more preferably 11 mol% to 11.5 mol%. The content of CeO2 is more preferably 14 mol% to 13 mol%, particularly preferably 12.5 mol% to 12 mol%. When the content of CeO2 is 10 mol% to 15 mol%, the mechanical strength of the zirconium oxide sintered body obtained by sintering the silver-containing stabilized zirconium oxide powder is better. Among them, the content of CeO2 is preferably 10 mol% to 14 mol%.

[0201] When zirconium oxide and the stabilizer are taken as a whole, if CeO2 is used as the stabilizer, the content of CeO2 is more preferably from 11 mol% to 14 mol%, further preferably from 11.5 mol% to 13 mol%, and particularly preferably from 11.5 mol% to 12.5 mol%.

[0202] When zirconium oxide and a stabilizer are taken as a whole, if any one of Sc2O3, Er2O3, and Yb2O3 is used as the stabilizer, its content is preferably 1.4 mol% or more and 7.5 mol% or less. When any one of Sc2O3, Er2O3, and Yb2O3 is used, the content is more preferably 1.5 mol% or more, and further preferably 1.6 mol% or more. When any one of Sc2O3, Er2O3, and Yb2O3 is used, the content is more preferably 6.5 mol% or less, further preferably 6 mol%, particularly preferably 5.6 mol% or less, particularly preferably 5 mol% or less, and particularly preferably 4.5 mol% or less. When the content of any one of Sc2O3, Er2O3, and Yb2O3 is 1.4 mol% or more and 7.5 mol% or less, the mechanical strength of the zirconium oxide sintered body obtained by sintering the silver-containing stabilized zirconium oxide powder is more excellent.

[0203] When zirconium oxide and the stabilizer are taken as a whole, if any one of Sc2O3, Er2O3, and Yb2O3 is used as the stabilizer, the content thereof is more preferably from 1.5 mol% to 6.5 mol%, and further preferably from 1.6 mol% to 6 mol%.

[0204] When zirconium oxide and a stabilizer are taken as a whole, if CaO is used as the stabilizer, the content of CaO is preferably 3.5 mol% or more and 15 mol% or less. The content of CaO is more preferably 3.8 mol% or more, and further preferably 4.0 mol% or more. The content of CaO is more preferably 12.0 mol% or less, and further preferably 9.0 mol% or less. When the content of CaO is 3.5 mol% or more and 15 mol% or less, the mechanical strength of the zirconium oxide sintered body obtained by sintering the silver-containing stabilized zirconium oxide powder is more excellent.

[0205] When zirconium oxide and the stabilizer are considered as a whole, if CaO is used as the stabilizer, the content of CaO is more preferably 3.8 mol % to 12 mol %, and further preferably 4 mol % to 9 mol %.

[0206] When zirconium oxide and stabilizer are taken as a whole, if CaO and Y2O3 are used as the stabilizer, the total amount of the stabilizer is 2.5 mol% to 6.5 mol% in terms of oxide, and the ratio of [CaO amount (mol%)] / [total amount of stabilizer (mol%)] is preferably 50% to 98%.

[0207] The ratio of [the amount of CaO (mol%)] / [the total amount of stabilizers (mol%)] is more preferably 55% or more, and further preferably 60% or more.

[0208] The ratio of [the amount of CaO (mol%)] / [the total amount of the stabilizer (mol%)] is more preferably 90% or less, and further preferably 80% or less.

[0209] The ratio of [amount of CaO (mol%)] / [total amount of stabilizer (mol%)] is more preferably 55% to 90%, and further preferably 60% to 80%.

[0210] When zirconium oxide and stabilizer are taken as a whole, if CaO and Y2O3 are used as the stabilizer, the total amount of the stabilizer is preferably 2.5 mol% or more and 6.5 mol% or less in terms of oxide. When the total amount of the stabilizer is 2.5 mol% or more in terms of oxide, the monoclinic phase ratio in the obtained zirconium oxide sintered body can be reduced, and cracking of the zirconium oxide sintered body obtained by sintering the zirconium oxide powder can be prevented. Moreover, when the total amount of the stabilizer is 6.5 mol% or less in terms of oxide, the cubic phase ratio with lower mechanical properties (strength, toughness) can be reduced, and the tetragonal phase ratio with higher mechanical properties can be increased.

[0211] The total amount of the stabilizer is preferably 2.7 mol % or more, more preferably 2.9 mol % or more, and further preferably 3.0 mol % or more, in terms of oxide.

[0212] The total amount of the stabilizer, calculated as oxide, is preferably 6.0 mol % or less, more preferably 5.5 mol % or less, further preferably 5.0 mol % or less, and particularly preferably 4.5 mol % or less.

[0213] The total amount of the stabilizer, calculated as oxide, is preferably 2.7 mol % to 6.0 mol %, more preferably 2.9 mol % to 5.5 mol %, further preferably 3.0 mol % to 5.0 mol %, particularly preferably 3.0 mol % to 4.5 mol %.

[0214] The silver-containing zirconium oxide powder may contain Al2O3 (aluminum oxide) in a range of 25% by mass or less when the total amount of zirconium oxide and the stabilizer is set to 100% by mass. When the alumina is contained in a range of 25% by mass or less, the alumina is used as a sintering aid in the process of sintering the zirconium oxide powder to obtain a silver-containing zirconium oxide sintered body.

[0215] If the silver-containing zirconia powder contains Al 2 O 3 , the content of Al 2 O 3 is more preferably 10% by mass or less, and further preferably 1% by mass or less, from the viewpoint of well exerting the function of a sintering aid.

[0216] If the silver-containing zirconia powder contains Al 2 O 3 , the content of Al 2 O 3 is more preferably 0.1% by mass or less, and further preferably 0.25% by mass or less, from the viewpoint of well exerting the function of a sintering aid.

[0217] When the silver-containing zirconia sintered body contains Al 2 O 3 , the content of Al 2 O 3 is more preferably 0.1 mass % to 10 mass %, and further preferably 0.25 mass % to 1 mass %.

[0218] When the aluminum oxide in the silver-containing stabilized zirconia powder is in the form of powder, the average particle size of the primary particles of the aluminum oxide is not particularly limited, and is, for example, 0.02 to 0.4 μm, preferably 0.05 to 0.3 μm, and more preferably 0.07 to 0.2 μm.

[0219] It should be noted that if the silver-containing stabilized zirconia powder has the following pore volume distribution, low-temperature sintering can be performed. Therefore, even if a sintering aid is not included, low-temperature sintering can be performed.

[0220] In order to improve the properties such as strength, the silver-containing stabilized zirconia powder may further contain sinterable ceramics and thermosetting resins in addition to alumina.

[0221] The silver-containing stabilized zirconia powder may contain one or more selected from the group consisting of Fe, V, Mn, Co, Cr, Tb, Zn, Cu and Ti. When one or more selected from the group consisting of Fe, V, Mn, Co, Cr, Tb, Zn, Cu and Ti are contained as coloring elements, a zirconia sintered body obtained by sintering the silver-containing stabilized zirconia powder can be well colored.

[0222] <Pore Distribution>

[0223] 1. Peak diameter of primary particle gap

[0224] In the range of 10 nm to 0.5 μm of the pore distribution based on the mercury intrusion method, the peak top diameter of the pore volume distribution of the silver-containing stabilized zirconia powder is preferably 20 nm to 200 nm. The peak top diameter is preferably 25 nm or more, more preferably 30 nm or more, further preferably 32 nm or more, and particularly preferably 35 nm or more. The peak top diameter is preferably 150 nm or less, more preferably 120 nm or less, further preferably 100 nm or less, and particularly preferably 85 nm or less.

[0225] The peak top diameter is preferably from 25 nm to 150 nm, and more preferably from 30 nm to 120 nm.

[0226] It should be noted that if there are multiple peaks in the range of 10 nm to 0.5 μm of the pore distribution, the "peak top diameter of the pore volume distribution is 20 nm to 200 nm" mentioned in this specification means that all peak top diameters in the range of 10 nm to 0.5 μm of the pore distribution are within the range of 20 nm to 200 nm.

[0227] 2. Pore distribution width of primary particle gap

[0228] The pore distribution width of the silver-containing stabilized zirconia powder is preferably 40 nm to 200 nm in the range of 10 nm to 0.5 μm of pore distribution based on mercury intrusion. The pore distribution width is preferably 43 nm to 43 nm, more preferably 46 nm to 46 nm, further preferably 50 nm to 55 nm, and particularly preferably 150 nm to 120 nm, further preferably 110 nm to 110 nm, particularly preferably 100 nm to 100 nm, and particularly preferably 80 nm to 80 nm.

[0229] The pore distribution width is preferably from 43 nm to 150 nm, and more preferably from 46 nm to 120 nm.

[0230] Here, the pore distribution width refers to the width of a peak having a log differential pore volume of 0.1 ml / g or more.

[0231] It should be noted that if there are multiple peaks in the range of 10 nm to 0.5 μm of the pore distribution, the "pore distribution width is 40 nm to 200 nm" mentioned in this specification means that, in a graph representing the pore distribution with the horizontal axis being the pore diameter and the vertical axis being the log integral pore volume, when observed from the smaller pore diameter side, the point that first intersects with the log integral pore volume of 0.1 mL / g (the point of rising intersection) is the minimum diameter, and the point that intersects with the log integral pore volume of 0.1 mL / g again (the point of falling intersection) is the maximum diameter, and the difference between the maximum diameter and the minimum diameter is 40 nm to 200 nm.

[0232] 3. Pore volume between primary particles

[0233] The pore volume of the silver-containing stabilized zirconia powder is preferably 0.2 ml / g or more but less than 0.5 ml / g in the range of 10 nm or more and 0.5 μm or less of the pore distribution based on the mercury intrusion method. The pore volume is preferably 0.22 ml / g or more, more preferably 0.25 ml / g or more, further preferably 0.3 ml / g or more, particularly preferably 0.35 ml / g or more, and particularly preferably 0.4 ml / g or more. The pore volume is preferably 0.48 ml / g or less, more preferably 0.46 ml / g or less, and particularly preferably 0.44 ml / g or less.

[0234] The pore volume is preferably 0.22 ml / g to 0.48 ml / g, and more preferably 0.25 ml / g to 0.46 ml / g.

[0235] The “range of 10 nm or more and 0.5 μm or less in pore distribution based on mercury intrusion porosimetry” refers to a range in which pores as primary particle gaps of the silver-containing stabilized zirconia powder can exist.

[0236] In the range of 10 nm to 0.5 μm of the pore distribution based on the mercury intrusion method, when the peak diameter of the pore volume distribution is 20 nm to 200 nm and the pore distribution width is 40 nm to 200 nm, the size of each pore (gap between each primary particle) is very small and arranged neatly (sharp distribution).

[0237] Therefore, the primary particles constituting the secondary particles are uniformly and tightly aggregated, and no large pores exist.

[0238] Among them, zirconium oxide particles (including primary particles and secondary particles) have the characteristic of being difficult to sinter when the pore volume is large. In other words, to sinter at a low temperature, not only the size of the pores originating from the gaps between the primary particles in the secondary particles needs to be small and sharply distributed, but also the volume of the pores originating from the gaps between the primary particles needs to be reduced.

[0239] Therefore, when the pore volume in the range of 10 nm to 0.5 μm based on the pore distribution determined by mercury intrusion porosimetry is greater than 0.2 ml / g but less than 0.5 ml / g, the pore volume originating from the gaps between the primary particles is small and there are no large pores, so a sintered body with a very high sintering density can be obtained.

[0240] By controlling the pore diameter, pore distribution and pore volume of the primary particle gaps in this way, low-temperature sintering can be performed and a sintered body with a very high sintering density can be obtained.

[0241] <Particle size D 50 >

[0242] The particle size D of the silver-containing stabilized zirconia powder 50 It is preferably 0.1 μm or more and 1.5 μm or less. 50 The particle size D is preferably 0.1 μm or more, more preferably 0.20 μm or more, further preferably 0.25 μm or more, and particularly preferably 0.30 μm or more. 50 It is preferably 1.2 μm or less, more preferably 1.0 μm or less, further preferably 0.8 μm or less, particularly preferably 0.7 μm or less, particularly preferably 0.6 μm or less, and particularly preferably less than 0.5 μm.

[0243] The particle size D of the silver-containing stabilized zirconia powder 50 The diameter is preferably 0.1 μm or more and 1.5 μm or less, and more preferably 0.20 μm or more and 1.0 μm or less.

[0244] The particle size D 50 is a value obtained according to the method described in the embodiment.

[0245] It should be noted that, during the measurement, the particle size D 50 The silver-stabilized zirconia powder contains not only secondary particles but also unagglomerated primary particles. The amount of unagglomerated primary particles contained in the silver-stabilized zirconia powder is extremely small. 50 It can be regarded as the particle size D of the secondary particles. 50 , that is, the average particle size of the secondary particles.

[0246] When the particle size D of the silver-containing stabilized zirconia powder is 50When the particle size is 1.5 μm or less, the secondary particle size is relatively small, so the gap between the secondary particles can be reduced. As a result, the low-temperature sintering property is excellent. Moreover, since the gap between the secondary particles is small, a sintered body with a high sintering density can be obtained.

[0247] <Specific surface area>

[0248] The specific surface area of ​​the silver-stabilized zirconia powder is preferably 5 m 2 / g above 60m 2 / g or less. The specific surface area is preferably 5m 2 / g or more, more preferably 9m 2 / g or more, more preferably 13m 2 / g or more, particularly preferably 15 m 2 / g or more. The specific surface area is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 35m 2 / g or less, particularly preferably 30m 2 / g or less.

[0249] The specific surface area of ​​the silver-containing stabilized zirconia powder is more preferably 9 m 2 / g above 40m 2 / g or less, more preferably 13m 2 / g above 35m 2 / g or less, particularly preferably 15m 2 / g above 30m 2 / g or less.

[0250] In order to sinter the stabilized zirconia powder at a lower temperature than the conventional temperature of about 1300°C to 1500°C, it is effective to increase the specific surface area. However, since it is difficult to control the particle growth rate during the process of manufacturing the stabilized zirconia powder, it is conventionally believed that the specific surface area should be less than 15 m 2 / g to prevent residual pores in the stabilized zirconia powder as much as possible.

[0251] On the other hand, if the primary particle gap can be controlled as described above, even if the specific surface area is set to 15m 2 / g or more silver-containing stabilized zirconia powder will not have a large number of pores remaining. 2 / g or more, the low temperature sintering property can be improved.

[0252] The specific surface area is a value obtained according to the method described in Examples.

[0253] The silver-containing stabilized zirconia powder according to the present embodiment has been described above.

[0254] [Method for producing silver-containing stabilized zirconia powder]

[0255] Hereinafter, an example of a method for producing a silver-containing stabilized zirconia powder will be described. However, the method for producing a silver-containing stabilized zirconia powder is not limited to the following example.

[0256] The method for producing the silver-containing stabilized zirconium oxide powder of this embodiment includes:

[0257] A step of mixing stabilized zirconium oxide containing zirconium oxide and a stabilizer with silver oxide having an average particle size of 0.5 μm or less.

[0258] The method for producing the silver-containing stabilized zirconium oxide powder preferably comprises:

[0259] Step 1, heating the zirconium salt solution and the sulfating agent solution to a temperature between 95° C. and 100° C. respectively;

[0260] Step 2, contacting the heated zirconium salt solution with the heated sulfating agent solution, wherein the concentration of the mixed solution does not change from the start to the end of the contact, thereby obtaining a reaction solution containing basic zirconium sulfate as a mixed solution;

[0261] Step 3, aging the reaction solution containing basic zirconium sulfate obtained in step 2 at a temperature above 95° C. for more than 3 hours;

[0262] Step 4, adding a stabilizer to the aged reaction solution containing basic zirconium sulfate obtained in step 3;

[0263] Step 5, adding a base to the reaction solution containing basic zirconium sulfate obtained in step 4 to obtain a zirconium-containing hydroxide;

[0264] Step 6, heat-treating the zirconium-containing hydroxide obtained in step 5 to obtain stabilized zirconium oxide; and

[0265] Step 7, mixing the stabilized zirconium oxide obtained in step 6 with silver oxide having an average particle size of 0.5 μm or less,

[0266] In the above step 2, from the start to the end of the contact, SO4 in the mixed solution 2- The weight ratio of ZrO / ZrO2 is maintained in the range of 0.3 to 0.8, and the temperature of the mixed solution is maintained above 95°C.

[0267] Hereinafter, each step will be described in detail.

[0268] <Process 1>

[0269] In step 1, the zirconium salt solution and the sulfating agent solution as starting materials are heated to 95° C. or higher and 100° C. or lower, respectively.

[0270] For example, zirconium oxynitrate, zirconium oxychloride, zirconium nitrate, etc. can be used as the zirconium salt for preparing the zirconium salt solution, as long as it is a zirconium salt that can provide zirconium ions. One or more of these zirconium salts can be used. Among them, zirconium oxychloride is preferred from the perspective of high productivity on an industrial scale.

[0271] The solvent used to prepare the zirconium salt solution may be selected according to the type of zirconium salt, etc. Water (pure water, ion-exchanged water, the same below) is usually preferred.

[0272] The concentration of the zirconium salt solution is not particularly limited. Generally speaking, the concentration of the zirconium salt solution is preferably 5 to 250 g, more preferably 20 to 150 g, in terms of zirconium oxide (ZrO2) in 1000 g of the solvent.

[0273] The sulfating agent may be, for example, sodium sulfate, potassium sulfate, ammonium sulfate, potassium hydrogen sulfate, sodium hydrogen sulfate, potassium pyrosulfate, sodium pyrosulfate, sulfur trioxide, etc., as long as it is a sulfating agent (i.e., a reagent for sulfation) that reacts with zirconium ions to generate sulfate. The sulfating agent may be in any form such as powder or solution, preferably a solution (especially an aqueous solution). As for the solvent, the same solvent as that used to prepare the zirconium salt solution may be used.

[0274] The acid concentration of the zirconium salt solution is preferably 0.1 to 2.0 N. By setting the acid concentration within the above range, the agglomeration state of the particles constituting the silver-containing stabilized zirconium oxide powder can be controlled in a better state. For example, the acid concentration can be adjusted using hydrochloric acid, nitric acid, sodium hydroxide, etc.

[0275] The concentration of the sulfating agent (the sulfating agent solution) is not particularly limited. Generally speaking, the concentration of the sulfating agent is preferably 5 to 250 g, and particularly preferably 20 to 150 g, per 1000 g of the solvent.

[0276] The material of the container for preparing the zirconium salt solution and the sulfation agent solution is not particularly limited, as long as it has a capacity that can fully stir the zirconium salt solution and the sulfation agent solution, respectively. However, it is preferred to have a device that can appropriately heat the solution so that the temperature of each solution is not less than 95°C.

[0277] The heating temperature of the zirconium salt solution and the sulfation agent solution may be 95° C. to 100° C., preferably 97° C. or higher. If step 2 is performed when the temperature of the zirconium salt solution and the sulfation agent solution is less than 95° C., the zirconium salt solution and the sulfation agent cannot react sufficiently, resulting in a decrease in yield.

[0278] <Process 2>

[0279] In step 2, the heated zirconium salt solution is contacted with the heated sulfating agent solution, but the concentration of the mixed solution does not change from the start to the end of the contact, thereby obtaining a reaction solution containing basic zirconium sulfate as a mixed solution. 2- The weight ratio of ZrO / ZrO2 is maintained in the range of 0.3 to 0.8, and the temperature of the mixed solution is maintained above 95°C.

[0280] Hereinafter, step 2 will be described with reference to the drawings.

[0281] Figure 1 Schematic diagram for explaining the method for producing silver-containing stabilized zirconia powder according to the present embodiment. Figure 1 As shown, the container 10 is connected to the upper end of the T-shaped pipe 20 through the valve 12 ( Figure 1 The container 30 is connected to the other end (the left side) of the T-shaped tube 20 through the valve 32. Figure 1 The container 10 stores a zirconium solution heated to 95°C or more and 100°C or less. The container 30 stores a sulfating agent solution heated to 95°C or more and 100°C or less.

[0282] In step 2, valves 12 and 32 are opened simultaneously to allow the zirconium solution and the sulfating agent solution to contact each other. The mixed solution obtained by the contact (reaction solution containing basic zirconium sulfate) immediately flows from the bottom of the T-tube 20 into the aging container 40. In step 2, this method ensures that the concentration of the reaction solution does not change from the beginning to the end of the contact between the zirconium solution and the sulfating agent solution (the concentration of the reaction solution in the T-tube 20). In step 2, the SO4 concentration at the beginning to the end of the contact is controlled. 2- / ZrO2 concentration changes, thereby obtaining a uniform reactant. By adopting such a process (process 2), the peak diameter, pore volume, and pore distribution width of the primary particles can be controlled. That is, the size of the pores originating from the gaps between the primary particles in the secondary particles can be made smaller and the distribution can be sharper, and further, the pore volume originating from the gaps between the primary particles can be reduced.

[0283] SO4 in the mixed liquid of step 2 2- The weight ratio of SO4 / ZrO2 is preferably in the range of 0.3 to 0.8, more preferably 0.4 to 0.7, and further preferably 0.45 to 0.65. 2- The yield of basic zirconium sulfate as a reaction product can be increased by making the SO4 in the mixed solution 2- The weight ratio of ZrO2 to ZrO2 is below 0.8, which can inhibit the formation of soluble salts in zirconium sulfate and inhibit the reduction in the yield of basic zirconium sulfate.

[0284] In step 2, in order to maintain the temperature of the mixed solution at 95° C. or higher, it is preferable to install a heater in the pipe (for example, T-tube 20 ) or the like for supplying each solution.

[0285] Hereinafter, an example of step 2 will be described in detail.

[0286] Use the upper end ( Figure 1 The diameter L1 of the tube is 10 mm, and the other end ( Figure 1 In the embodiment of the present invention, a T-tube 20 is a T-tube having a tube diameter L2 of 10 mm at the top (in the right side) and a tube diameter L3 of 15 mm at the bottom. When 213 g of a 25 mass % sodium sulfate aqueous solution and 450 g of a 16 mass % zirconium oxychloride aqueous solution as calculated as ZrO2 are brought into contact, the time (contact time) from the start of contact to the end of contact (until the zirconium chloride aqueous solution in container 10 and the sulfation agent solution in container 30 are exhausted) is preferably 30 seconds to 300 seconds, more preferably 60 seconds to 200 seconds, and even more preferably 90 seconds to 150 seconds.

[0287] <Process 3>

[0288] In step 3, the reaction liquid containing basic zirconium sulfate obtained in step 2 is aged at 95°C or above for 3 hours or more. In step 3, for example, the reaction liquid containing basic zirconium sulfate flowing into the aging container 40 is stirred by a stirrer 42 and aged at 95°C or above for 3 hours or more. There is no particular limit to the upper limit of the aging time, for example, it is 7 hours or less. The temperature (aging temperature) of the mixed solution (reaction liquid containing basic zirconium sulfate) in step 3 is preferably above 95°C, and more preferably above 97°C and below 100°C. By setting the aging temperature to be above 95°C and the aging time to be above 3 hours, basic zirconium sulfate can be fully generated and the yield can be improved.

[0289] It should be noted that the mixed solution contains basic zirconium sulfate as a main component and is a basic zirconium sulfate slurry.

[0290] <Step 4>

[0291] In step 4, a stabilizer is added to the aged reaction solution containing basic zirconium sulfate obtained in step 3.

[0292] <Step 5>

[0293] In step 5, a base is added to the reaction solution containing basic zirconium sulfate obtained in step 4 to perform a neutralization reaction. By the neutralization, a zirconium-containing hydroxide is generated.

[0294] The alkali is not limited, and may be, for example, caustic soda, sodium carbonate, ammonia, hydrazine ammonium bicarbonate, etc. The concentration of the alkali is not particularly limited, and is usually used at 5 to 30% by dilution with water.

[0295] There are two methods for adding the alkali: (1) adding an alkali solution to a reaction solution containing basic zirconium sulfate, and (2) adding a reaction solution containing basic zirconium sulfate, but there are no particular limitations and either method may be used.

[0296] After neutralization, the slurry is filtered to obtain a zirconium-containing hydroxide. If necessary, the zirconium-containing hydroxide is preferably washed with pure water to remove impurities. After washing, it can be dried if necessary.

[0297] <Step 6>

[0298] In step 6, the zirconium-containing hydroxide obtained in step 5 is heat-treated (fired) to oxidize the zirconium-containing hydroxide, thereby obtaining stabilized zirconium oxide.

[0299] The heat treatment temperature (firing temperature) and the heat treatment time (firing time) of the zirconium-containing hydroxide are not particularly limited, and are usually carried out at about 600 to 1050°C for 1 to 10 hours. The firing temperature is more preferably 650°C to 1000°C, and more preferably 700°C to 980°C. The firing temperature is more preferably 2 hours to 6 hours, and more preferably 2 hours to 4 hours. By setting the heat treatment temperature to 600°C to 1200°C, the specific surface area of ​​the obtained stabilized zirconium oxide can be controlled within a preferred range (for example, 5 m 2 / g above 60m 2 The heat treatment atmosphere is not particularly limited, and it may be usually air or an oxidizing atmosphere.

[0300] <Step 7>

[0301] In step 7, the stabilized zirconium oxide obtained in step 6 is mixed with silver oxide having an average particle size of 0.5 μm or less. During the mixing process, the stabilized zirconium oxide powder and the silver oxide may be slurried to homogenize them. Thus, a silver-containing stabilized zirconium oxide powder is obtained.

[0302] <Step 8>

[0303] After step 7, the obtained silver-containing stabilized zirconia powder may be pulverized and slurried, if necessary. At this time, a binder may be added to improve the moldability. If the slurry is not formed (if the pulverization is not performed), the binder and the silver-containing stabilized zirconia powder may be uniformly mixed using a kneader.

[0304] The binder is preferably an organic binder. Since the organic binder can be easily removed from the molded body in a heating furnace in an oxidizing atmosphere to obtain a degreased body, impurities are unlikely to remain in the sintered body in the end.

[0305] The organic binder may be an alcohol-soluble binder or an adhesive soluble in a mixture of two or more selected from the group consisting of alcohol, water, aliphatic ketones and aromatic hydrocarbons. The organic binder may be at least one selected from the group consisting of, for example, polyethylene glycol, ethylene glycol fatty acid ester, glycerol fatty acid ester, polyvinyl butyral, polyvinyl methyl ether, polyvinyl ethyl ether and vinyl propionate. The organic binder may also contain one or more thermoplastic resins insoluble in alcohol or the above-mentioned mixture.

[0306] After the organic binder is added, the mixture may be dried, crushed, or treated by a known method to obtain the desired silver-containing stabilized zirconia powder.

[0307] The particle size D of the silver-containing stabilized zirconia powder can be controlled by the pulverization in step 8. 50 For example, the particle size D of the silver-containing stabilized zirconia powder can be controlled by pulverizing the powder according to the state of the silver-containing stabilized zirconia powder obtained in step 5. 50 .

[0308] The silver-containing stabilized zirconia powder after step 7 is a silver-containing stabilized zirconia powder containing stabilized zirconia and silver oxide, and generally does not contain silver. After step 7, all or part of the silver oxide is decomposed into silver by heating. For example, after step 7, the heat in the drying process decomposes all or part of the silver oxide into silver.

[0309] Thus, according to the method for producing silver-containing stabilized zirconia powder of this embodiment,

[0310] (1) After step 7, if heating is not performed, a silver-containing stabilized zirconia powder containing stabilized zirconia and silver oxide having an average particle size of 0.5 μm or less but not containing silver is obtained.

[0311] (2) After step 7, if the mixture is heated to a degree that a part of the silver oxide is decomposed, a silver-containing stabilized zirconium oxide powder containing stabilized zirconium oxide, silver having an average particle size of 0.5 μm or less, and silver oxide is obtained.

[0312] (3) After step 7, when the mixture is heated to a degree that the silver oxide is completely decomposed, a silver-containing stabilized zirconia powder containing stabilized zirconia and silver having an average particle size of 0.5 μm or less but not containing silver oxide is obtained.

[0313] When a sintering aid, a colorant, etc. are added, they are added and mixed in step 7 to obtain a silver-containing stabilized zirconia powder containing the sintering aid, the colorant, etc. A more detailed mixing method is preferably wet mixing, in which the mixture is dispersed in pure water or the like to form a slurry.

[0314] In addition, when performing the step 7, a sintering aid, a coloring agent, etc. may be added during the step 7.

[0315] The silver-containing stabilized zirconia powder according to the present embodiment has been described above.

[0316] [Method for producing zirconia sintered body]

[0317] Hereinafter, an example of the method for producing a zirconia sintered body will be described. However, the method for producing a zirconia sintered body of the present invention is not limited to the following example.

[0318] The method for producing a zirconia sintered body according to the present embodiment includes:

[0319] Step X, molding the silver-containing stabilized zirconia powder to obtain a molded body; and

[0320] Step Y is, after the step X, sintering the molded body at a temperature of 1250° C. to 1500° C. for 1 hour to 5 hours.

[0321] In the method for producing a zirconia sintered body of the present embodiment, first, a silver-containing stabilized zirconia powder is prepared. As the silver-containing stabilized zirconia powder, the silver-containing stabilized zirconia powder described in [Silver-Containing Stabilized Zirconia Powder] can be used.

[0322] Next, the silver-containing stabilized zirconia powder is molded to obtain a molded body (process X). The molding can be performed using a commercially available mold molding machine or cold isostatic pressing (CIP). In addition, after the silver-containing stabilized zirconia powder is pre-molded using a mold molding machine, it can be formally molded by stamping. Stamping is usually performed at 0.1t to 3t / cm 2 It is preferably within the range of 0.5t to 2.5t / cm 2 , more preferably 0.8t~2.2t / cm 2 , more preferably 1t~2t / cm 2 .

[0323] Next, the molded body is sintered under the conditions of 1250° C. to 1500° C. for 1 hour to 5 hours (step Y).

[0324] In the present embodiment, since the silver-containing stabilized zirconia powder is used, the sintering temperature can be set to a low temperature of 1250 to 1500°C. The sintering temperature is more preferably 1300°C to 1450°C, and particularly preferably 1350°C to 1400°C. The holding time during sintering is not particularly limited, and for example, is preferably about 1 to 5 hours, and more preferably 1 to 3 hours. The sintering atmosphere may be in the air or in an oxidizing atmosphere. Sintering can be performed at normal pressure without the need for deliberate pressurization.

[0325] It should be noted that if silver oxide remains in the silver-containing stabilized zirconia powder, all of the silver oxide is thermally decomposed into silver by the sintering step (step Y). It should be noted that depending on the sintering conditions, a portion (eg, a very small amount) of silver oxide may remain.

[0326] In summary, a silver-containing zirconia sintered body containing silver particles, zirconium oxide and a stabilizer can be obtained, wherein the average particle size of the silver particles is less than 0.5 μm, the average grain size of the stabilized zirconia is less than 0.35 μm, and the relative sintering density is more than 98%.

[0327] The method for producing the zirconia sintered body according to the present embodiment has been described above.

[0328] Example

[0329] The present invention is described in detail below with reference to the examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the present invention. It should be noted that the silver-containing stabilized zirconia powder and the silver-containing zirconia sintered body in the examples and comparative examples contain 1 to 3 mass % (calculated by the following formula (X)) of hafnium as an inevitable impurity relative to zirconium.

[0330] <Formula (X)>

[0331] ([Mass of hafnium oxide] / ([Mass of zirconium oxide]+[Mass of hafnium oxide]))×100(%)

[0332] The maximum and minimum values ​​of the content of each component shown in the following examples are irrelevant to the contents of other components and should be regarded as the preferred minimum and preferred maximum values ​​of the present invention.

[0333] Furthermore, the maximum and minimum values ​​of the measured values ​​shown in the following examples have nothing to do with the content (composition) of each component, and should be regarded as the preferred minimum and maximum values ​​of the present invention.

[0334] [Preparation of silver-stabilized zirconia powder]

[0335] (Example 1)

[0336] 213 g of a 25 mass % sodium sulfate aqueous solution and 450 g of a 16 mass % zirconium oxychloride aqueous solution (acid concentration: 1 N) in terms of ZrO 2 were heated to 95° C., respectively (step 1).

[0337] Then, the heated aqueous solutions were brought into contact with each other for 2 minutes so that the SO4 2- / ZrO2 mass ratio reaches 0.50 (process 2).

[0338] Next, the obtained reaction liquid containing basic zirconium sulfate was maintained at 95° C. for 4 hours and aged to obtain basic zirconium sulfate (step 3).

[0339] Next, after the aged solution is cooled to room temperature, an aqueous solution of yttrium chloride in an amount of 10% by mass as Y2O3 is added and uniformly mixed so that the Y2O3 content reaches 3.2 mol% (step 4).

[0340] Next, a 25% by mass sodium hydroxide aqueous solution was added to the obtained mixed solution to neutralize it until the pH reached 13 or more, thereby generating a hydroxide precipitate (step 5).

[0341] Specifically, the combination Figure 1 The described apparatus performs the above operations.

[0342] The obtained hydroxide precipitate was filtered and washed thoroughly with water. The obtained hydroxide was heat-treated in air at 1000° C. (firing temperature) for 4 hours to obtain unpulverized stabilized zirconium oxide (yttria-stabilized zirconium oxide powder) (step 6).

[0343] Silver oxide powder (manufactured by Mitsuwa Chemicals Co., Ltd., product name: Silver Oxide (I), average particle size: 20 μm) was added to the un-crushed stabilized zirconium oxide in an amount of 1% by mass relative to the stabilized zirconium oxide, and then alumina powder with an average particle size of 0.1 μm of primary particles was added in an amount of 0.5% by mass relative to the stabilized zirconium oxide, and the mixture was pulverized and mixed in a wet ball mill with water as a dispersion medium for 40 hours (step 7). φ5 mm zirconium oxide beads were used for pulverization. The zirconia slurry obtained after pulverization was dried at 110°C to obtain the silver-containing stabilized zirconium oxide powder described in Example 1.

[0344] (Example 2 to Example 5)

[0345] The silver-containing stabilized zirconia powders of Examples 2 to 5 were obtained in the same manner as in Example 1, except that the amount of silver oxide added was changed to that shown in Table 1, no alumina powder was added, and the firing temperature was changed to 850°C.

[0346] (Example 6)

[0347] The silver-containing stabilized zirconia powder of Example 6 was obtained in the same manner as in Example 1 except that the alumina powder was not added and the firing temperature was changed to 1150°C.

[0348] (Example 7)

[0349] The silver-containing stabilized zirconia powder of Example 7 was obtained in the same manner as in Example 1 except that the alumina powder was not added and the firing temperature was changed to 830°C.

[0350] (Example 8)

[0351] The same powder as the silver-containing stabilized zirconia powder of Example 3 is the silver-containing stabilized zirconia powder of Example 8.

[0352] (Example 9 to Example 10)

[0353] The silver-containing stabilized zirconia powders of Examples 9 and 10 were obtained in the same manner as in Example 1, except that the amount of Y2O3 added was changed to that shown in Table 1 and the firing temperature was changed to 850°C.

[0354] (Example 11)

[0355] The silver-containing stabilized zirconia powder of Example 11 was obtained in the same manner as in Example 1, except that an aqueous yttrium chloride solution was not added, an erbium chloride solution was added at 10 mass % as Er2O3 to make Er2O3 reach 3.2 mol %, and the firing temperature was changed to 850°C.

[0356] (Example 12)

[0357] The silver-containing stabilized zirconia powder of Example 12 was obtained in the same manner as in Example 1, except that an aqueous yttrium chloride solution was not added, an aqueous cerium chloride solution was added at 12 mass % of CeO2 to make the CeO2 reach 12 mol %, and the amount of aluminum oxide powder added was changed to 0.25 mass %.

[0358] (Example 13)

[0359] The silver-containing stabilized zirconia powder of Example 13 was obtained in the same manner as in Example 1, except that an aqueous yttrium chloride solution was added to make the Y2O3 content reach 0.9 mol%, 2.1 mol% of calcium carbonate (CaCO3) was added, and alumina powder was not added, and the firing temperature was changed to 950°C.

[0360] (Example 14)

[0361] The silver-containing stabilized zirconia powder of Example 14 was obtained in the same manner as in Example 1 except that the amount of the aluminum oxide powder added was changed to 20 mass % and the firing temperature was changed to 850°C.

[0362] (Comparative Example 1)

[0363] 213 g of a 25 mass % sodium sulfate aqueous solution and 450 g of a 16 mass % zirconium oxychloride aqueous solution (acid concentration: 1 N) in terms of ZrO 2 were heated to 95° C., respectively (step 1).

[0364] Then, the heated aqueous solutions were brought into contact with each other for 2 minutes so that the SO4 2- / ZrO2 mass ratio reaches 0.50 (process 2).

[0365] Next, the obtained reaction liquid containing basic zirconium sulfate was maintained at 95° C. for 4 hours and aged to obtain basic zirconium sulfate (step 3).

[0366] Next, after the aged solution is cooled to room temperature, an aqueous solution of yttrium chloride in an amount of 10% by mass as Y2O3 is added and uniformly mixed so that the Y2O3 content reaches 3.2 mol% (step 4).

[0367] Next, a 25% by mass sodium hydroxide aqueous solution was added to the obtained mixed solution to neutralize it until the pH reached 13 or more, thereby generating a hydroxide precipitate (step 5).

[0368] Specifically, the combination Figure 1 The described apparatus performs the above operations.

[0369] The obtained hydroxide precipitate was filtered and washed thoroughly with water. The obtained hydroxide was heat-treated in air at 850° C. (firing temperature) for 4 hours to obtain unpulverized stabilized zirconium oxide (yttria-stabilized zirconium oxide powder) (step 6).

[0370] Silver powder (manufactured by Mitsuwa Chemicals Co., Ltd., product name: Silver (particles), particle size: 2-4 μm) was added to the obtained un-crushed stabilized zirconium oxide in an amount of 1 mass % relative to the stabilized zirconium oxide, and the mixture was crushed and mixed in a wet ball mill with water as a dispersion medium for 40 hours (step 7). φ5 mm zirconium oxide beads were used for crushing. The zirconium oxide slurry obtained after crushing was dried at 110° C. to obtain the silver-containing stabilized zirconium oxide powder of Example 1.

[0371] (Comparative Example 2)

[0372] Silver (powder) (~525 mesh) 99% manufactured by Mitsuwa Chemicals Co., Ltd. was heat treated at 400°C for 2 hours to increase the particle size. A silver-containing stabilized zirconia powder of Comparative Example 2 was obtained in the same manner as in Example 3 except that the obtained silver powder was used.

[0373] [Determination of the composition of silver-stabilized zirconia powder]

[0374] The compositions (calculated as oxide) of the silver-containing stabilized zirconia powders of Examples and Comparative Examples were analyzed using ICP-AES ("ULTIMA-2" manufactured by HORIBA).

[0375] [Measurement of Particle Size of Silver Particles and / or Silver Oxide Particles in Silver-Containing Stabilized Zirconia Powder]

[0376] The COMPO images of the silver-stabilized zirconia powders of the embodiments and comparative examples were obtained using the SEM "Phenom Pro-x" (manufactured by Phenom world). The Heywood diameter of the silver oxide particles or silver particles was determined using the image analysis software "Image-Pro" (manufactured by Media Cybernetics). Specifically, the outline of the silver particles was manually outlined (drawn) on the image analysis software, the area of ​​the outlined silver particles was measured, and converted into the Heywood diameter. A total of 10 Heywood diameters were measured, and the average particle size was calculated. The results are shown in Table 1.

[0377] [Measurement of specific surface area of ​​silver-stabilized zirconia powder]

[0378] The specific surface areas of the silver-containing stabilized zirconia powders of Examples and Comparative Examples were measured by the BET method using a specific surface area meter ("Macsorb" manufactured by MOUNTECH).

[0379] [Particle size D of silver-stabilized zirconia powder 50 Determination of

[0380] 0.15 g of the silver-stabilized zirconium oxide powder of the example and the comparative example and 40 ml of a 0.2% sodium hexametaphosphate aqueous solution were placed in a 50 ml beaker, dispersed in an ultrasonic homogenizer "Sonifier-S-450D" (Emerson Co., Ltd., Japan) for 5 minutes, and then placed in an apparatus (laser diffraction particle size distribution measuring apparatus ("SALD-2300" manufactured by Shimadzu Corporation, Japan)) for measurement. The results are shown in Table 1.

[0381] [Measurement of pore volume of silver-containing stabilized zirconia powder]

[0382] The pore distribution of the zirconium oxide powders of the examples and comparative examples was obtained by mercury intrusion porosimetry using a pore distribution measuring device ("Autopore IV9500" manufactured by Micromeritics). The measuring conditions are as follows:

[0383] <Measurement conditions>

[0384] Measurement device: pore distribution measurement device (Autopore IV9500 manufactured by Micromeritics);

[0385] Measuring range: 0.0036~10.3μm;

[0386] Measurement points: 120 points;

[0387] Mercury contact angle: 140 degrees;

[0388] Mercury surface tension: 480 dyne / cm.

[0389] The obtained pore distribution was used to determine the peak top diameter, pore volume, and pore distribution width in the range of 10 nm to 0.5 μm. The results are shown in Table 1.

[0390] Here, the pore distribution width refers to the width of a peak having a log differential pore volume of 0.1 ml / g or more.

[0391] [Preparation of zirconia sintered body]

[0392] First, the molded bodies of the zirconium oxide powders of the examples and comparative examples were obtained by cold isostatic pressing (CIP). The molding pressure was 2 t / cm 2 .

[0393] At this time, the relative molding density of the molded body was determined as follows.

[0394] Next, the molded body was sintered at the "sintering temperature" shown in Table 2 for 2 hours to obtain a silver-containing zirconia sintered body.

[0395] It should be noted that the silver-containing zirconia sintered body of Comparative Example 3 is a silver-containing zirconia sintered body obtained by sintering the silver-containing stabilized zirconia powder of Comparative Example 2 at a sintering temperature of 1550° C. As in the silver-containing stabilized zirconia powder of Comparative Example 2, when the silver particles are large, it is necessary to sinter at 1550° C. to achieve densification, but for the silver-containing zirconia sintered body of Comparative Example 3 obtained by sintering the silver-containing stabilized zirconia powder of Comparative Example 2 at a sintering temperature of 1550° C., the hydrothermal aging resistance is poor due to the increased sintering temperature.

[0396] <Relative sintered density>

[0397] The relative sintered density is the relative sintered density expressed by the following formula (1):

[0398] Relative sintered density (%) = (sintered density / theoretical sintered density) × 100···(1).

[0399] The theoretical sintered density (denoted as ρ0) is the value calculated by the following formula (2-1):

[0400] ρ0=(100+Y+Z) / [(100 / ρz)+(Y / 3.987)+(Z / 10.49)]···(2-1).

[0401] Wherein, Y is the aluminum oxide concentration (weight %), and Z is the silver concentration (weight %). When silver oxide is used as a raw material, the silver concentration (weight %) is calculated according to formula (2-2):

[0402] Z = [107.868 × silver oxide concentration (weight %)] / (231.736 × 2)···(2-2).

[0403] ρz is the value calculated by the following formula (2-3):

[0404] ρz=[124.25(100-X)+[molecular weight of stabilizer]×X] / 150[150.5(100+X)A 2 C]···(2-3).

[0405] Among them, if the stabilizer is Y2O3, the molecular weight of the stabilizer is 225.81, if the stabilizer is Er2O3, the molecular weight of the stabilizer is 382.52, and if the stabilizer is Yb2O3, the molecular weight of the stabilizer is 394.11.

[0406] In addition, X is the stabilizer concentration (mol %). And, A and C are values ​​calculated by the following formulas (2-4) and (2-5), respectively:

[0407] A=0.5080+0.06980X / (100+X)···(2-4);

[0408] C=0.5195-0.06180X / (100+X)···(2-5).

[0409] In formula (1), the theoretical sintered density varies depending on the powder composition.

[0410] For example, if the yttria content is 2 mol%, the theoretical sintered density of yttria-containing zirconium oxide is 6.117 g / cm 3If the yttria content is 3 mol%, the theoretical sintered density of yttria-containing zirconium oxide is 6.098 g / cm 3 If the yttria content is 5.5 mol%, the theoretical sintered density of yttria-containing zirconium oxide is 6.051 g / cm 3 (If Al2O3=0 weight %).

[0411] If the stabilizer is Sc2O3, ρz is the value calculated by the following formula (3):

[0412] ρz=-0.0402(molar concentration of Sc2O3)+6.1294···(3).

[0413] If the stabilizer is CaO, ρz is the value calculated by the following formula (3-1):

[0414] ρz=-0.0400(molar concentration of CaO)+6.1700···(3-1).

[0415] In addition, the theoretical sintered density (denoted as ρ1) when a colorant is included is:

[0416] ρ1=100 / [(Z / V)+(100-Z) / ρ0]···(2-5).

[0417] In addition, Z is the colorant concentration (weight %), V is the colorant theoretical density (g / cm 3 ).

[0418] The theoretical density of the colorant is: Fe2O3 is 5.24g / cm 3 , ZnO is 5.61g / cm 3 , MnO2 is 5.03g / cm 3 , CoO is 6.10 g / cm 3 , Cr2O3 is 5.22g / cm 3 , TiO2 is 4.23g / cm 3 , Tb4O7 is 7.80g / cm 3 , CuO is 6.31 g / cm 3 , V2O5 is 3.36g / cm 3 .

[0419] In addition, the sintered density was measured by the Archimedean method.

[0420] <Relative molding density>

[0421] Relative molding density (%) = (molding density / theoretical sintering density) × 100···(4)

[0422] The theoretical sintered density (denoted as ρ0) is a value calculated by the above formula (2-1).

[0423] [Particle Size of Silver Particles in Silver-Containing Zirconia Sintered Body]

[0424] The surfaces of the sintered bodies of the embodiments and comparative examples were ground and polished to expose the silver-containing parts, and a COMPO image was obtained using the SEM "Phenom Pro-x" (manufactured by Phenom world). The Heywood diameter of the silver particles was determined using the image analysis software "Image-Pro" (manufactured by Media Cybernetics). Specifically, the outline of the silver particles was manually outlined (drawn) on the image analysis software, the area of ​​the outlined silver particles was measured, and converted into the Heywood diameter. A total of 100 Heywood diameters were measured, and the average particle size of the silver particles was calculated. The results are shown in Table 2.

[0425] [Average grain size of stabilized zirconia in silver-containing zirconia sintered body]

[0426] The grain sizes of the stabilized zirconia in the zirconia sintered bodies of Examples and Comparative Examples were determined as follows.

[0427] The SEM observation image of the sintered body sample obtained by scanning electron microscope observation was obtained. The sample for SEM observation was adjusted based on JIS R1633. The SEM observation image is set to have more than 150 grains in one field of view. Draw a rectangle of any size in the SEM observation image, and calculate the number of particles on the sides and diagonals of the rectangle. In the embodiments and comparative examples, a rectangle of 3.497μm×2.375μm was drawn at a magnification of 30,000 times. Each side of the rectangle is set to a length of more than 80% of the field of view. The average grain size is calculated based on the number of particles and the length of the four sides and diagonals of the rectangle.

[0428] Specifically, the average grain size was calculated according to the following formula:

[0429] (Average grain size) = {[X / (x1+x2)]+[Y / (y1+y2)]+[D / (d1+d2)]}×2 / 3.

[0430] It should be noted that, in the formula, X, x1, x2, Y, y1, y2, D, d1, and d2 are expressed as follows:

[0431] X (μm): length of the long side of the rectangle;

[0432] Y (μm): length of the short side of the rectangle;

[0433] D (μm): length of the diagonal of the rectangle;

[0434] x1 (pieces): the number of particles on a long side;

[0435] x2 (pieces): the number of particles on the other long side;

[0436] y1(pieces): the number of particles on a short edge;

[0437] y2(pieces): the number of particles on the other short side;

[0438] d1 (pieces): the number of particles on a diagonal line;

[0439] d2 (pieces): the number of particles on the other diagonal line.

[0440] The same operation was performed for three fields of view at each level, and the average grain size of the three fields of view was taken as the final average grain size.

[0441] It should be noted that before the measurement, the sintered body samples were mirror-polished and then pre-treated by thermal etching. The mirror-polishing was performed by grinding the sintered body surface with a surface grinder and then polishing with diamond abrasive grains with average particle sizes of 9 μm, 6 μm, and 3 μm in a mirror-polishing device.

[0442] [Monoclinic phase ratio of silver-containing zirconia sintered body after hydrothermal treatment at 134°C and 0.3 MPa for 15 hours]

[0443] First, the silver-containing zirconia sintered bodies of the examples and comparative examples obtained above were hydrothermally treated at 134° C. and an absolute pressure of 0.3 MPa (in water atmosphere) for 15 hours. Then, the monoclinic phase ratio contained in the crystal phase of the silver-containing zirconia sintered bodies after the hydrothermal treatment was determined.

[0444] The silver-containing zirconia sintered bodies of the examples and comparative examples after hydrothermal treatment were mirror-polished to obtain the monoclinic phase ratio contained in the crystal phase. The mirror-polishing was performed by grinding the surface of the sintered body with a surface grinder and then polishing with diamond abrasive grains with average particle sizes of 9 μm, 6 μm, and 3 μm in a mirror-polishing device. The results are shown in Table 2.

[0445] Specifically, the monoclinic phase ratio of the silver-containing zirconia sintered body of each example and comparative example was determined according to the following [Identification of Crystal Phase].

[0446] [Identification of crystal phase]

[0447] An X-ray diffraction spectrum of the silver-containing zirconia sintered body was obtained using an X-ray diffraction apparatus ("RINT2500" manufactured by Rigaku Corporation). The measurement conditions are as follows:

[0448] <Measurement conditions>

[0449] Measurement apparatus: X-ray diffraction apparatus (manufactured by Rigaku Corporation, “RINT2500”);

[0450] Line source: CuKα line source;

[0451] Sampling interval: 0.02°;

[0452] Scanning speed: 2θ = 1.0° / min;

[0453] Divergence slit (DS): 1°;

[0454] Divergence longitudinal limiting slit: 5mm;

[0455] Scattering slit (SS): 1°;

[0456] Light receiving slit (RS): 0.3mm;

[0457] Monochromatic light receiving slit: 0.8mm;

[0458] Tube voltage: 50kV;

[0459] Tube current: 300mA;

[0460] Scanning speed: 2θ=26~36°: 4° / min;

[0461] 2θ=72~76°:1° / min.

[0462] Then, the crystal phase was identified based on the X-ray diffraction spectrum. The phase ratio of each crystal phase contained in the silver-containing zirconia sintered body was calculated using the following calculation formula:

[0463] Monoclinic phase ratio (%) = (Im (111) + Im (11-1)) / (Im (111) + Im (11-1) + It (101) + Ic (111)) × 100;

[0464] Tetragonal phase ratio (%) = (100% - monoclinic phase (%)) × ((It (004) + It (220) / (It (004) + It (220) + Ic (004)) × 100;

[0465] Cubic crystal phase ratio (%) = (100% - monoclinic phase (%)) × ((Ic (004) / (It (004) + It (220) + Ic (004)) × 100.

[0466] Here, Im(111) is the diffraction intensity of the monoclinic phase (111), and Im(11-1) is the diffraction intensity of the monoclinic phase (11-1).

[0467] It(101) is the diffraction intensity of (101) of the tetragonal crystal phase, It(220) is the diffraction intensity of (220) of the tetragonal crystal phase, and It(004) is the diffraction intensity of (004) of the tetragonal crystal phase.

[0468] Ic(004) is the diffraction intensity of (004) of the cubic crystal phase, and Ic(111) is the diffraction intensity of (111) of the cubic crystal phase.

[0469] The monoclinic phase of zirconium oxide was distinguished from the tetragonal phase and the cubic phase near 2θ=26-36° in the XRD spectrum. The tetragonal phase and the cubic phase were distinguished near 2θ=72-76° in the XRD spectrum. The cubic phase may be deformed due to the amount of stabilizer added and the production process, and the peak position may also shift, but in this embodiment, the peak between (004) and (220) of the tetragonal phase is regarded as the peak of the cubic phase and calculated.

[0470] [toughness]

[0471] The toughness of the silver-containing zirconia sintered bodies of the examples and comparative examples obtained above was determined as follows.

[0472] The toughness measurement according to the IF method is carried out with a load of 30 kgf (294.2 N) in accordance with JIS R1607 (Test method for fracture toughness of fine ceramics at room temperature). Using a Vickers hardness tester, seven indentations with a quadrilateral shape are selected and their toughness is calculated. The average value of the toughness of the five indentations other than the indentations with the smallest and largest values ​​is taken as the toughness value. However, if the crack of the indentation does not extend, the measured indentation is invalid, and the indentation with four cracks extending from the front end of the quadrilateral is used.

[0473] Each toughness value is calculated by the following formula:

[0474] Kc=0.018×Hv×a 0.5 ×[(ca) / a] -0.5 ×(Hv / E) -0.4 .

[0475] The meanings of Kc, Hv, a, c, and E are as follows. When solving a and c, the indentation length of the X and Y axes and the crack length of the X and Y axes are referred to Figure 2 As shown:

[0476] Kc: Toughness value [MPa·m 0.5 ]

[0477] Hv: Vickers hardness [GPa]

[0478] a: Half of the average value of the indentation length of the X and Y axes [μm]

[0479] c: Half of the average value of the crack lengths on the X and Y axes [μm]

[0480] E: Young's modulus [GPa]

[0481] Vickers hardness is determined in accordance with JIS R 1610 (hardness test method for fine ceramics). Vickers hardness is calculated by the following formula:

[0482] Hv=0.001854×[F / d 2 Sv].

[0483] The meanings of F and d are as follows. When solving for d, the X-axis indentation length and the Y-axis indentation length refer to Figure 2 As shown:

[0484] Hv: Vickers hardness [GPa];

[0485] F: test force [N];

[0486] d: Average value of the X-axis indentation length and the Y-axis indentation length [mm].

[0487] As the Young's modulus, 210 GPa, which is known as a value of common yttria-stabilized zirconia, was used.

[0488] [3-point bending strength]

[0489] The three-point bending strength of the silver-containing zirconia sintered bodies of the examples and comparative examples obtained above was measured based on the three-point bending strength of JIS R 1601. The results are shown in Table 2.

[0490] Table 1

[0491]

[0492] Table 2

[0493]

Claims

1. A silver-containing zirconium oxide sintered body, characterized in that: Include: Silver particles; as well as Stabilized zirconium oxide, comprising zirconium oxide and a stabilizer, wherein: The average particle size of the silver particles is less than 0.5 μm, The average grain size of the stabilized zirconium oxide is less than 0.35 μm. The relative sintering density is above 98%.

2. The silver-containing zirconia sintered body according to claim 1, characterized in that The average grain size of the stabilized zirconia is less than 0.25 μm.

3. The silver-containing zirconia sintered body according to claim 1 or 2, characterized in that: When the total amount of zirconium oxide and the stabilizer is 100 mass %, the silver particles are contained in a range of 0.025 mass % to 20 mass % as Ag 2 O.

4. The silver-containing zirconia sintered body according to claim 1 or 2, characterized in that: The three-point bending strength is 600 MPa or more.

5. The silver-containing zirconia sintered body according to claim 1 or 2, characterized in that: The toughness value according to the IF method is 5MPa·m 0.5 above.

6. The silver-containing zirconia sintered body according to claim 1 or 2, characterized in that: The monoclinic crystal ratio after hydrothermal treatment at 134° C. and 0.3 MPa for 15 hours was 10% or less.

7. The silver-containing zirconia sintered body according to claim 1 or 2, characterized in that: The stabilizer is one or more selected from the group consisting of Y2O3, CeO2, Er2O3 and CaO.

8. The silver-containing zirconia sintered body according to claim 1 or 2, characterized in that: When zirconium oxide and the stabilizer are taken as a whole, the content of the stabilizer is 15 mol% or less.

9. A silver-stabilized zirconium oxide powder, characterized in that: Include: Stabilized zirconium oxide, comprising zirconium oxide and a stabilizer; and Silver and / or silver oxide having an average particle size of 0.5 μm or less.

10. The silver-stabilized zirconium oxide powder according to claim 9, characterized in that Within the range of 10 nm to 0.5 μm of pore distribution based on mercury porosimetry, the peak top diameter of pore volume distribution is 30 nm to 100 nm, the pore volume is 0.25 ml / g to 0.46 ml / g, and the pore distribution width is 40 nm to 120 nm.

11. A method for producing silver-containing stabilized zirconium oxide powder, comprising: A step of mixing stabilized zirconium oxide containing zirconium oxide and a stabilizer with silver oxide having an average particle size of 0.5 μm or less.

12. A method for producing a silver-containing zirconium oxide sintered body, characterized in that: include: Step X, forming the silver-containing stabilized zirconia powder according to claim 9 or 10 to obtain a formed body; and Step Y is, after the step X, sintering the molded body at a temperature of 1250° C. to 1500° C. for 1 hour to 5 hours.